Detection of Antichlamydial Immunoglobulin G and M Antibodies by Enzyme-Linked Immunosorbent Assay - Mahony, J. B. (1983)
Chlamydia trachomatis causes a wide range of infections in adults and conjunctivitis and pneumonia in neonates. The complement fixation test for chlamydial antibody is broadly reactive, but possesses low sensitivity, whereas the microimmunofluorescence test is highly sensitive, but technically difficult to perform. A simple, rapid enzyme-linked immunosorbent assay (ELISA) has been developed for the measurement of immunoglobulin G (IgG) and IgM antibodies to C. trachomatis. Wells of microtiter plates were coated with Renografin-purified elementary bodies (serotype L2) grown in cycloheximide-treated McCoy cells, and serum antibody was detected with peroxidase-labeled goat antihuman IgG and IgM antibody. Of 41 sera tested from patients with lymphogranuloma venereum, pelvic inflammatory disease, cervicitis, or urethritis there was a 90 and 63% correlation of positive results for IgG and IgM, respectively, by microimmunofluorescence and ELISA. Of the positive correlates, ELISA titers were up to 128 times higher than microimmunofluorescence titers for IgG and IgM. The ELISA detected no false-positive results, but missed two positive results for IgG. Both of these sera were reactive against serotypes C and J, suggesting that the ELISA with LGV L2 antigen may not measure antibodies to serotypes within the C serogroup. The IgM ELISA detected 7 negative and 4 positive results not detected by the microimmunofluorescence test. Of four paired sera examined by ELISA, three showed a fourfold rise in IgG antibody titer, and one showed a twofold rise. Further evaluation of this ELISA will be required to determine how useful it will be in seroepidemiological studies and as a diagnostic tool.